Integration and regionalization of the modern entrepreneurial activity: challenges for Russia and Eastern Europe - Erokhin, Vasily (Economics of Agriculture, 2010)
Integration in the world trading system fundamentally depends on whether policies and institutions are established in a country and its trading partners which are conducive to the mutually beneficial exchange of goods and services based on specialization and comparative advantage. Trade integration processes became more active after 1950s in all over the world. Today the separate country is not more able to control the competitive struggle between enterprises and countries, new spheres of competitiveness on the traditional markets. Effective integration of the economies in transition thus, involves not only their own trade policies and institutions but also those of their trading partners which affect market access and the terms of trade.